Transient photovoltage and dark current analysis on enhanced open-circuit voltage of polymer solar cells with hole blocking TiO2 nanoparticle interfacial layer - Kim, Youn-Su; Kim, Taehee; Kim, BongSoo; Lee, Doh-Kwon; Kim, Honggon; Ju, Byeong-Kwon; Kim, Kyungkon (ELSEVIER, 2013)
The open-circuit voltage of bulk heterojunction polymer solar cells utilizing 1,8-diiodooctane (DIO) as a processing additive was greatly improved by using an organic layer coated TiO2 nanoparticle interfacial layer inserted between the active layer and the Al electrode. The transient photovoltage measurement revealed that there was significant non-geminate recombination at the DIO-processed active layer/Al electrode interface. Reduced open-circuit voltage (V-OC) of the photovoltaic devices and high water contact angle of the DIO-processed active layer showed that the DIO-processed active layer has an undesirable surface composition for the electron collection. The organic layer coated TiO2 nanoparticle interfacial layer effectively prevented the non-geminate recombination at the active layer/Al interface. As a result, we were able to significantly improve the V-OC and power conversion efficiency from 0.46 V and 2.13% to 0.62 V and 3.95%, respectively. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: PHASE-SEPARATION; EFFICIENCY; RECOMBINATION; FILMS; DETERMINANT; ADDITIVES; BLEND